Pelatihan Branding Bagi Peserta Kursus Menjahit Yayasan Pendidikan Adhiputeri Makassar - Hamidah Suryani; Nurhijrah; Ridwan, Wardimansyah; Fitry Purnamasari; Jusuf, Luthfiani (Jurnal Edukasi dan Pengabdian kepada Masyarakat, 2025)
Sewing courses organized by the Adhiputeri Education Foundation in Makassar have equipped 20 participants with technical skills, yet these skills are not fully supported by the ability to build a brand and promote products digitally. Limited understanding of branding concepts, visual identity, and the use of social media makes their products less competitive and mostly confined to local markets. This community service program aims to enhance participants’ knowledge and skills in designing brand identity and managing digital promotion. The method employed consists of participatory training and mentoring through interactive lectures, discussions, demonstrations, and hands-on practice in creating logos and promotional materials using Canva, followed by simulated use of social media platforms. The results indicate improved understanding of branding, the ability to design logos and digital promotional materials, and increased confidence in marketing products through online platforms. Overall, the program contributes to strengthening economic independence based on sewing skills.